The search for Life on Mars and the Solar System - Strategies, Logostics and Infrastructures - de Vera, J. P.; Baque, Mickael; Billi, D.; Böttger, Ute; Bulat, S.; Czupalla, Markus; Dachwald, B.; de la Torre Noetzel, R.; Elsaesser, A.; Foucher, F.; Korsitzky, Hartmut; Kozyrovska, N.; et al. (2018)
The question "Are we alone in the Universe?" is perhaps the most fundamental one that affects mankind. How can we address the search for life in our Solar System? Mars, Enceladus and Europa are the focus of the search for life outside the terrestrial biosphere. While it is more likely to find remnants of life (fossils of extinct life) on Mars because of its past short time window of the surface habitability, it is probably more likely to find traces of extant life on the icy moons and ocean worlds of Jupiter and Saturn. Nevertheless, even on Mars there could still be a chance to find extant life in niches near to the surface or in just discovered subglacial lakes beneath the South Pole ice cap. Here, the different approaches for the detection of traces of life in the form of biosignatures including prebiotic molecules will be presented. We will outline the required infrastructure for this enterprise and give examples of future mission concepts to investigate the presence of life on other planets and moons. Finally, we will provide suggestions on methods, techniques, operations and strategies for preparation and realization of future life detection missions.